Strategi Pengembangan Obyek Wisata Aua Sarumpun oleh Dinas Pariwisata Pemuda dan Olahraga Kabupaten Tanah Datar - Suci Mutia; Jumiati Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The purpose of this study is to describe the strategy of the Tanah Datar Youth and Sports Tourism Office in developing Aua Sarumpun Tourism Object, to describe the inhibiting and supporting factors in the development of Aua Sarumpun Tourism Object. This research is processed by qualitative analysis techniques with descriptive methods, for data collection techniques through interviews, observation and documentation. Based on the results of research and discussion , it was found that the strategy for developing Aua Sarumpun tourism objects by the Youth and Sports Tourism Office was only by promoting using social media such as Instagram and Facebook and holding one event such as the Camp Art Festival which was held in August 2020 as well as in terms of facilities and infrastructure to pave the road approximately 300 meters. In terms of developing Aua Sarumpun tourism objects, there are still obstacles faced by the Tourism, Youth and Sports Office of Tanah Datar Regency.